Globalization and general worker training - Hans Gersbach; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2004)
We examine how globalization affects firms incentives to train workers. In our model, firms invest in productivity-enhancing worker training before Cournot competition takes place. When two separated product markets become integrated and are thus replaced with a market with greater demand and greater firm number, training by each firm increases provided the two countries are sufficiently small. When barriers between large markets are eliminated, training is reduced. Similar results hold when firms in countries with different training systems face globalization of product markets. In particular, apprenticeship systems are threatened by a large-scale integration of product markets. Contrary to product market integration, labor market integration has no effect on training incentives.
Keywords: D42; L22; L43; L92; 330; general training; human capital; oligopoly; turnover; Globalisierung; Humankapital; Betriebliches Bildungsmanagement; Oligopol; Marktstruktur; Theorie